Added prognostic value of Doppler ultrasound for adverse perinatal outcomes: A pooled analysis of three cohort studies. (9th June 2022) - Flanagan, Madeline F.; Vollgraff Heidweiller‐Schreurs, Charlotte A.; Li, Wentao; Ganzevoort, Wessel; de Boer, Marjon A.; Vazquez‐Sarandeses, Alicia; Turan, Ozhan M.; Bossuyt, Patrick M.; Mol, Ben W.J.; Rolnik, Daniel L.
Abstract : Background: Fetal growth restriction (FGR) is an obstetric complication associated with adverse perinatal outcomes. Doppler ultrasound can improve perinatal outcomes through monitoring at‐risk fetuses and helping time delivery. Aim: To investigate the prognostic value of different Doppler ultrasound measurements for adverse perinatal outcomes. Materials: Individual participant data. Methods: We performed a pooled analysis on individual participant data. We compared six prognostic models using multilevel logistic regression, where each subsequent model added a new variable to a base model that included maternal characteristics. Estimated fetal weight (EFW) and four Doppler ultrasound measurements were added in turn: umbilical artery pulsatility index (UA PI), middle cerebral artery pulsatility index (MCA PI), cerebroplacental ratio (CPR), and mean uterine artery pulsatility index (mUtA PI). The primary outcome was a composite adverse perinatal outcome, defined as perinatal mortality, emergency caesarean delivery for fetal distress, or neonatal admission. Discriminative ability was quantified with area under the curve (AUC). Results: Three data sets ( N  = 3284) were included. Overall, the model that included EFW and UA PI improved AUC from 0.650 (95% CI 0.624–0.676) to 0.673 (95% CI 0.646–0.700). Adding more ultrasound measurements did not improve further the discriminative ability. In subgroup analysis, the addition of EFW and UA PI improved AUC in both preterm (AUC from 0.711 to 0.795) and small for gestational age pregnancies (AUC from 0.729 to 0.770), but they did not improve the models in term delivery or normal growth subgroups. Conclusions: Umbilical artery pulsatility index added prognostic value for adverse perinatal outcomes to the already available information, but the combination of other Doppler ultrasound measurements (MCA PI, CPR or UtA PI) did not improve further prognostic performance.